An unprecedented large mesonephric cyst posing diagnostic dilemma and surgical challenge - Pushpalatha, Kameshwarachari; Mishra, Pritinanda; Bag, Nerbadyswari Deep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Mesonephric cyst is a vestigial remnant of the Wolffian duct in females. Occasionally, the mesonephric duct persists lateral to the vagina and uterus, and cystic lesions may sometimes develop into neoplastic lesions. Mesonephric cysts are very rare. Here we report an unprecedented large left broad ligament mesonephric cyst in a 27 year old lady that posed diagnostic and surgical challenges. Ultrasound findings included cystic swelling probably arising from left ovary suggestive of left ovarian cyst. Plain abdominal computed tomography scan showed large simple left paraovarian cystic mass with no solid areas. During laparotomy, we found a large left thin walled cyst with smooth external surface with vascular prominence measuring 20x13x11 cm arising within the broad ligament stretching the left Fallopian tube, close to left ovary and adherent to recto-sigmoid. Cystectomy was done with preservation of left ovary. Histopathology report was consistent with mesonephric cyst. Mesonephric duct cyst should be considered in the diagnosis of abdomino-pelvic masses in females of adolescent and early reproductive age.